Variations of wave energy power in shoaling zone of Benin coastal zone - Mathias A. Houekpoheha; Basile B. Kounouhewa; Joël T. Hounsou; Bernard N. Tokpohozin; Jean V. Hounguevou; Cossi. N. Awanou (Center of Biomass & Renewable Energy (CBIORE), 2015)
Today, we observe at the population level, that the improvement in comfort is accompanied by an increase in the electrical energy required. The predicted exhaustion of fossil energy resources maintains some speculation. Their unequal geographical distribution justifies the energy dependence of Benin overlooked from outside. So it is urgent to explore the various sources of renewable energy available to Benin. In this work, using measurements made ​​by the Millennium Challenge Account (MCA-Benin) as part of the extension of the port of Cotonou, with Boussinesq equations (Peregrine) and Stokes waves dispersion relation, we characterized the variations of various swell parameters (height, wavelength, velocities) in the shoaling zone on the study site and proceeded to estimate variations in wave energy power from deep waters to the bathymetric breaking point. Finally, the zone with high energy power (where the conversion of this energy into electrical energy would be profitable) of these waves is highlighted on the site, the local water depth at the point of breaking waves is evaluated and results obtained allowed to justify the very energetic character take by these swells on this coast when they are close to the beach.